Numeracy Literacy Course Learning Evaluation for Teacher Education Students – Early Childhood Education - Ragil, Yoga Aditia; Puji Astuti, Reni Intan (Universitas Islam Negeri Raden Intan Lampung, 2023)
Literacy and numeracy are one of the government's focuses in developing human resources in Indonesia. According to several studies, Indonesia ranks lower in literacy and numeracy. In one of the efforts to improve human resources in Indonesia regarding literacy and numeracy, the government makes regulations in implementing literacy and numeracy in education. The method used is qualitative, with a program evaluation approach to obtain materials for preparing literacy and numeracy learning strategies. Participants in this study were ten students consisting of three classes at Muhammadiyah University Jakarta, who were surveyed using a questionnaire related to their knowledge and understanding of numeracy literacy. The results show that much needs to be prepared in the literacy and numeracy learning process from both the lecturer and student perspectives because there are obstacles when learning literacy and numeracy in terms of preparation, learning, and evaluation. In addition, support from relevant stakeholders is also very much needed in collaboration to create a complete understanding